The Role of FT/TFL1 Clades and Their Hormonal Interactions to Modulate Plant Architecture and Flowering Time in Perennial Crops - Lillian Magalhães Azevedo; Raphael Ricon de Oliveira; Antonio Chalfun-Junior (Plants)
Human nutrition is inherently associated with the cultivation of vegetables, grains, and fruits, underscoring the critical need to understand and manipulate the balance between vegetative and reproductive development in plants. Despite the vast diversity within the plant kingdom, these developmental processes share conserved and interconnected pathways among angiosperms, predominantly involving age, vernalization, gibberellin, temperature, photoperiod, and autonomous pathways. These pathways interact with environmental cues and orchestrate the transition from vegetative growth to reproductive stages. Related to this, there are two key genes belonging to the same Phosphatidylethanolamine-binding proteins family (PEBP), the FLOWERING LOCUS T (FT) and TERMINAL FLOWER 1 (TFL1), which activate and repress the floral initiation, respectively, in different plant species. They compete for transcription factors such as FLOWERING LOCUS D (FD) and 14-3-3 to form floral activation complexes (FAC) and floral repression complexes (FRC). The FT/TFL1 mechanism plays a pivotal role in meristem differentiation, determining developmental outcomes as determinate or indeterminate. This review aims to explore the roles of FT and TFL1 in plant architecture and floral induction of annual and perennial species, together with their interactions with plant hormones. In this context, we propose that plant development can be modulated by the response of FT and/or TFL1 to plant growth regulators (PGRs), which emerge as potential tools for mitigating the adverse effects of environmental changes on plant reproductive processes. Thus, understanding these mechanisms is crucial to address the challenges of agricultural practices, especially in the face of climate change.